Pelatihan Motivasi Berprestasi sebagai Strategi Meningkatkan Kompetensi Sosial-Emosional pada Generasi Z - Putri W, Riyan; Nazihatun, Indana; Khotimah, Khusnul; Hafifah, Nur (Keris: Journal of Community Engagement, 2024)
This service is designed to explore the effectiveness of the Achievement Motivation Seminar in enhancing students' enthusiasm and readiness to face academic challenges. The main focus of this service is to analyze the impact of the Achievement Motivation Seminar on the development of students' abilities in setting goals, planning their next steps, and enhancing their emotional resilience. The subjects of this research are 65 fifth and sixth-grade students who are actively involved in the Seminar process. The method used in this service is Participatory Action Research (PAR), with an approach of direct observation, in-depth interviews, and data analysis. The results of the service show a significant improvement in students who attended the achievement motivation seminar, which can be seen before and after the seminar was held. To achieve optimal results, there needs to be a relationship between the guidance counselor and subject teachers who consistently provide good and creative guidance and teaching in the classroom. Therefore, for future community service research, it can be expanded and creatively thought out to provide achievement motivation so that students can truly implement it.